Right Circulant Matrices with Geometric Progression - Bueno, Aldous Cesar (International Journal of Applied Mathematical Research, 2012)
In this paper, the right circulant matrix with geometric progression is investigated and its inverse is obtained. The eigenvalues, determinant, Euclidean norm, and spectral norm of both and are determined. Some examples are provided to illustrate the obtained results.